2012
DOI: 10.1111/ecc.12014
|View full text |Cite
|
Sign up to set email alerts
|

Does communication skills training make a difference to patients' experiences of consultations in oncology and palliative care services?

Abstract: There is much evidence supporting the efficacy of communication skills training; however, very little of this evidence comes from patient feedback. The primary aim of this pilot study was to evaluate whether the advanced communications skills training improves patients' experience of consultations. Healthcare professionals working in oncology and palliative care services from the North East of England were invited to participate in this study. Interactions between healthcare professionals (n = 21) and patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 23 publications
(54 reference statements)
0
22
0
Order By: Relevance
“…Such a review is also necessary because, although communication training tends to produce ‘improvements' that communication experts value, evidence for its effectiveness when assessed from patients' perspectives is mixed (Shilling et al , 2003; Lobb et al , 2004; Uitterhoeve et al , 2010; Tulsky et al , 2011; Johnson et al , 2013). Oncologists in our study allocated considerable time to explaining instrumental aspects of care and this was a crucial source of comfort for many parents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a review is also necessary because, although communication training tends to produce ‘improvements' that communication experts value, evidence for its effectiveness when assessed from patients' perspectives is mixed (Shilling et al , 2003; Lobb et al , 2004; Uitterhoeve et al , 2010; Tulsky et al , 2011; Johnson et al , 2013). Oncologists in our study allocated considerable time to explaining instrumental aspects of care and this was a crucial source of comfort for many parents.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, studies of patient–oncologist consultations indicate that such communication is the exception rather than the rule (Pollak et al , 2007; Hack et al , 2010; Rodriguez et al , 2010), prompting calls for more communication training for oncologists. However, beyond its possible role in identifying those patients experiencing pathological distress, evidence that patients find it helpful to discuss their emotions with oncologists is inconclusive (Lobb et al , 2004; Uitterhoeve et al , 2010; Tulsky et al , 2011; Johnson et al , 2013). Moreover, theory that explains how explicit emotionality in medical consultations helps patients to regulate their fears is lacking (Pedersen, 2009; Hack et al , 2010).…”
mentioning
confidence: 99%
“…Yet, despite these observed relationships, there are far fewer studies demonstrating the impact of communication-focused interventions on patients' and relatives' experiences and outcomes 66. One commonly cited explanation for this is inappropriate measurement tools that lack sensitivity to change 67 68. This is problematic, as without confidence in the measures used to assess intervention effectiveness, including responsiveness to change,69 we cannot discern whether lack of effect is associated with inadequate training or inappropriate outcomes.…”
Section: What Can We Do To Improve End-of-life Care Communication?mentioning
confidence: 99%
“…A second explanation frequently encountered for a lack of change is ceiling effects—where high baseline scores make improvements difficult to obtain. Ceiling effects have been found in a number of interventions, including some aiming to improve patient perceptions of clinicians' empathy and communication skills,68 and ratings of therapeutic alliance65 and satisfaction 61 70. These high baseline scores raise questions as to whether intervention studies are targeting the most appropriate settings, or recruiting healthcare providers and/or patients in ways that introduce bias (eg, including those more willing to talk about end-of-life care at baseline).…”
Section: What Can We Do To Improve End-of-life Care Communication?mentioning
confidence: 99%
“…However, while palliative care communication skills training programmes improve providers’ communication skills,2 preliminary studies indicate that training does not affect patient-reported outcomes 3. This randomised trial examined the relationship between provider participation in a palliative care communication skills training programme, and patient-reported, family-reported and healthcare provider-reported outcomes.…”
Section: Contextmentioning
confidence: 99%